Zen and the art of producing - Mixerman (Milwaukee, WI : Hal Leonard Books, 2012)
"Explores the many roles and responsibilities of a music producer and offers advice on music production"--Provided by publisher.
Keywords: Sound recording executives and producers -- Vocational guidance; Popular music -- Production and direction